2014
DOI: 10.1080/17470218.2014.923922
|View full text |Cite
|
Sign up to set email alerts
|

Feature overlap slows lexical selection: Evidence from the picture–word interference paradigm

Abstract: How does the presence of a categorically related word influence picture naming latencies? In order to test competitive and noncompetitive accounts of lexical selection in spoken word production, we employed the picture–word interference (PWI) paradigm to investigate how conceptual feature overlap influences naming latencies when distractors are category coordinates of the target picture. Mahon et al. (2007. Lexical selection is not by competition: A reinterpretation of semantic interference and facilitation ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
2
26
2
1
Order By: Relevance
“…This suggests that distinctive feature activation does not predominate in the presence of activation from many shared features (e.g., Cree et al, 2006), and so does not influence production of the target name. This finding can be accommodated by existing competitive lexical selection (Vigliocco et al, 2004; Rahman and Melinger, 2009; Vieth et al, 2014) and response exclusion accounts (e.g., Mahon et al, 2007). In the former, feature overlap predominates and activates a lexical cohort with the net result being competition; in the latter, identical response relevant criteria result in the post-lexical decision mechanism taking more time to clear both types of distractor from the articulatory buffer.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This suggests that distinctive feature activation does not predominate in the presence of activation from many shared features (e.g., Cree et al, 2006), and so does not influence production of the target name. This finding can be accommodated by existing competitive lexical selection (Vigliocco et al, 2004; Rahman and Melinger, 2009; Vieth et al, 2014) and response exclusion accounts (e.g., Mahon et al, 2007). In the former, feature overlap predominates and activates a lexical cohort with the net result being competition; in the latter, identical response relevant criteria result in the post-lexical decision mechanism taking more time to clear both types of distractor from the articulatory buffer.…”
Section: Discussionmentioning
confidence: 77%
“…Further, Sailor and Brooks (2014) were unable to replicate the findings from Costa et al's (2005) second experiment using identical materials. In two separate PWI experiments, Vieth et al (2014) were likewise unable to replicate the facilitation effect reported by Mahon et al (2007; Experiment 7) using near identical stimuli based on feature production norms (McRae et al, 2005). Instead, they found reliably greater interference for distractors that shared more features with the target.…”
Section: Introductionmentioning
confidence: 87%
“…Not all semantic neighbors exert equal effects, as close semantic neighbors will compete to a greater extent than distant semantic neighbors. For example, naming a picture of a dog is frequently slower in the presence of a near semantic neighbor (e.g., cat) than a distant semantic neighbor (e.g., whale) or an unrelated distractor (e.g., couch; see Damian et al, 2001;Fieder et al, 2018;Rose et al, 2018;Vieth et al, 2014; but see Mahon, Costa, Peterson, Vargas, & Caramazza, 2007). The semantic properties that influence neighborhood distance may plausibly include shape, size, color, typical location, or other taxonomic or event-related (thematic) features.…”
Section: Discussionmentioning
confidence: 99%
“…In the domains of language and semantic memory, considerable evidence suggests that the sharing of semantic (e.g., visual or propositional) or phonological features influences competition. For example, the word "robin" may interfere with the production of the word "ostrich" by virtue of the sharing of visual and propositional feature "has wings" (e.g., see Collins & Loftus, 1975;Fieder, Wartenburger, & Abdel Rahman, 2018;Mirman & Magnuson, 2008;Rose, Aristei, Melinger, & Abdel Rahman, 2018;Vieth, McMahon, & de Zubicaray, 2014;Vigliocco, Vinson, Lewis, & Garrett, 2004); as representations with shared features are more likely to compete for selection (Damian, Vigliocco, & Levelt, 2001;Luce & Pisoni, 1998;Magnuson, Dixon, Tanenhaus, & Aslin, 2007;Vigliocco et al, 2004; for review, see Chen & Mirman, 2012). Furthermore, research in patients with language deficits demonstrates that competition among neighboring word representations is exacerbated in the presence of lesions to the left inferior frontal gyrus (IFG), resulting in a greater number of selection-related errors in picture naming tasks (e.g., see Ries, Karzmark, Navarrete, Knight, & Dronkers, 2015;Schnur et al, 2009;Thompson-Schill et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this notion, Mahon et al (2007) reported a stronger interference effect for semantically distant distractors (e.g., target: horse, distractor: whale) than semantically close distractors (e.g., target: horse, distractor: zebra). However, growing evidence has shown a contrasting finding that stronger interference was observed in close distractors as opposed to distant ones (Vigliocco et al, 2002;Vieth et al, 2014;Rose et al, 2019). Besides, a null effect for lexical cohort size has been reported as well (Hutson and Damian, 2014).…”
Section: The Influence Of Lexical Cohort Size On Semantic Context Effmentioning
confidence: 99%